25 years of HBM in the Czech Republic - Černá, Milena; Puklová, Vladimíra; Hanzlíková, Lenka; Sochorová, Lenka; Kubínová, Růžena (International journal of hygiene and environmental health, 2017)
Since 1991 a human biomonitoring network has been established in the Czech Republic as part of the Environmental Health Monitoring System, which was set out by the Government Resolution. During the last quarter-century, important data was obtained to characterize exposure to both children and adult populations to significant toxic substances from the environment, to development trends over time, to establish reference values and compare them with existing health-related values. Moreover, the saturation of population with several essential substances as selenium, zinc, copper or iodine has also been monitored. Development of analytical and statistical methods led to increase the capacity building, improvement of QA/QC in analytical laboratories and interpretation of results. The obtained results are translated to policy actions and are used in health risk assessment processes at local and national levels.
Keywords: Environmental Monitoring; Male; monitorování životního prostředí; Česká republika; Child; látky znečišťující životní prostředí; Milk, Human; dítě; Adult; dospělí; mužské pohlaví; vlasy, chlupy; Czech Republic; lidé; ženské pohlaví; Humans; Environmental Pollutants; mateřské mléko; Female; Hair